2015
DOI: 10.1097/md.0000000000002143
|View full text |Cite
|
Sign up to set email alerts
|

Early Statin Use and the Progression of Alzheimer Disease

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
67
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(69 citation statements)
references
References 35 publications
2
67
0
Order By: Relevance
“…Moreover, cholesterol and plasma membrane lipid contents have been shown to control Aβ production by interfering with enzyme activity [116]. The use of cholesterol-lowering medication such as statins was able to reduce Aβ production in an AD mouse model [118] and AD progression in patients [119]. High doses of simvastatin reduced the cerebral levels of Aβ and Aβ in the cerebrospinal fluid and brain of guinea pig [120].…”
Section: Alzheimer's Diseasementioning
confidence: 99%
“…Moreover, cholesterol and plasma membrane lipid contents have been shown to control Aβ production by interfering with enzyme activity [116]. The use of cholesterol-lowering medication such as statins was able to reduce Aβ production in an AD mouse model [118] and AD progression in patients [119]. High doses of simvastatin reduced the cerebral levels of Aβ and Aβ in the cerebrospinal fluid and brain of guinea pig [120].…”
Section: Alzheimer's Diseasementioning
confidence: 99%
“…Table S2 shows the two RCTs 30,31 and three cohort-style studies. 4,32,33 Neither RCT ran for long enough to collect outcomes at 2 years (both were 72 wk) and are therefore only included for adverse events. All studies covered only dementia of the AD type.…”
Section: Resultsmentioning
confidence: 99%
“…Seven cohort studies (Chen et al, ; Chuang, Lin, Lin, Sung, & Kao, ; Hendrie et al, ; Hippisley‐Cox & Coupland, ; Li et al, ; C.‐K. Wu et al, ; Yang et al, ) and five case control studies (Booker et al, ; Chen, Liu, Chen, & Wu, ; Corrao et al, ; Horsdal et al, ; Lin et al, ) found that statin use was associated with a reduced risk of dementia. According to these studies, beginning treatment with high doses of lipophilic statins before an early old age (<80 years old) and taking these statins for a long time might reduce the risk of dementia.…”
Section: Resultsmentioning
confidence: 99%
“…Drugs that act through different mechanisms mostly unrelated to their principal pharmacological properties could potentially modulate cognitive performance (Nevado-Holgado, Kim, Winchester, Gallacher, & Lovestone, 2016). On the one hand, many drugs known to decrease vascular risk factors, such as statins, antihypertensive medications (AHMs), and antidiabetics, could have a beneficial effect on cognition (Imfeld, Bodmer, Jick, & Meier, 2012;Lin et al, 2015;Yasar et al, 2016). On the other hand, many drugs are known to increase the risk of dementia (either degenerative dementia or vascular dementia) and cognitive decline.…”
mentioning
confidence: 99%